IPDeN: Real-Time deflection-based NoC with in-order flits delivery - Ribot González, Yilian (2022)
In deflection-based Network-on-Chips (NoC), when several flits entering a router contend for the same output port, one of the flits is routed to the desired output and the others are deflected to alternatives outputs. The approach reduces power consumption and silicon footprint in comparison to virtual channels (VCs) based solutions. However, due to the nondeterministic number of deflections that flits may suffer while traversing the network, flits may be received in an out-of-order fashion at their destinations. In this work, we present IPDeN, a novel deflectionbased NoC that ensures in-order flit delivery. To avoid the use of costly reordering mechanisms at the destination of each communication flow, we propose a solution based on a single small buffer added to each router to prevents flits from over taking other flits belonging to the same communication flow. We also develop a worst-case traversal time (WCTT) analysis for packets transmitted over IPDeN. We implemented IPDeN in Verilog and synthesized it for an FPGA platform. We show that a router of IPDeN requires "483-times less hardware resources than routers that use VCs. Experimental results shown that the worst-case and average packets communication time is reduced in comparison to the state-of-the-art